Female reproductive health impacts of Long COVID and associated illnesses including ME/CFS, POTS, and connective tissue disorders: a literature review - Pollack, Beth; von Saltza, Emelia; McCorkell, Lisa; Santos, Lucia; Hultman, Ashley; Cohen, Alison K.; Soares, Letícia (Frontiers in Rehabilitation Sciences, 2023)
Long COVID disproportionately affects premenopausal women, but relatively few studies have examined Long COVID’s impact on female reproductive health. We conduct a review of the literature documenting the female reproductive health impacts of Long COVID which may include disruptions to the menstrual cycle, gonadal function, ovarian sufficiency, menopause, and fertility, as well as symptom exacerbation around menstruation. Given limited research, we also review the reproductive health impacts of overlapping and associated illnesses including myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), postural orthostatic tachycardia syndrome (POTS), connective tissue disorders like Ehlers-Danlos syndrome (EDS), and endometriosis, as these illnesses may help to elucidate reproductive health conditions in Long COVID. These associated illnesses, whose patients are 70%-80% women, have increased rates of dysmenorrhea, amenorrhea, oligomenorrhea, dyspareunia, endometriosis, infertility, vulvodynia, intermenstrual bleeding, ovarian cysts, uterine fibroids and bleeding, pelvic congestion syndrome, gynecological surgeries, and adverse pregnancy complications such as preeclampsia, maternal mortality, and premature birth. Additionally, in Long COVID and associated illnesses, symptoms can be impacted by the menstrual cycle, pregnancy, and menopause. We propose priorities for future research and reproductive healthcare in Long COVID based on a review of the literature. These include screening Long COVID patients for comorbid and associated conditions; studying the impacts of the menstrual cycle, pregnancy, and menopause on symptoms and illness progression; uncovering the role of sex differences and sex hormones in Long COVID and associated illnesses; and addressing historical research and healthcare inequities that have contributed to detrimental knowledge gaps for this patient population.